The quantum model of the development of intelligence as a theoretical basis of the theory of technological development. Construction technology life cycles - Osipov, A. (Ways to Improve Construction Efficiency, 2024)
The article outlines the main provisions and analyses the main models of intelligence development using a historical approach. A quantum model of intelligence development is proposed, which reveals the logical essence of intellectual processes occurring at the levels of individual and integral intelligence. Individual and integral intelligences can remain in stationary states for a long time, in which the intelligence and the system of intelligences have "volumes". Any change in the "volume" of intelligence occurs only with a complete transition from one state to another, the mechanism of intellectual transitions is a discrete process. It is shown that the pattern of growth of the "volume" of integral intelligence obeys the exponential law. The volume of integral intelligence increases like an intellectual flash; the process of development of integral intelligence is discrete, cyclical and has a constant parameter – the lag of integral intelligence, which belongs to the interval of 6–8 years. The relationship between the development cycles of integral intelligence (its outbursts) and "Kondratiev’s big cycles" is established. For each lag of integral intelligence, its "volume" increases, relative to the initial level, by the value of the exponent, and each "great Kondratiev cycle" has from 6 to 8 lags of integral intelligence, which precede waves of technical inventions and their practical application in the form of innovations, that is, innovative products and technologies. The development of construction technologies is a continuous and irreversible process of increasing their effectiveness over time, and is generally described by s-shaped curves that are tangent to the contour curve characterizing the integral effectiveness of public labor in the construction industry. Technologies have their own life cycles, consisting of stages that differ in the level of relative effectiveness, namely: the stage of introduction and initial diffusion, the stage of maximum diffusion, the stage of rationalization, the stage of obsolescence. The existence of technologies at the stage of aging is impractical.